New in vitro biomarkers to detect toxicity in human placental cells: The example of benzo[A]pyrene. (April 2016) - Wakx, Anaïs; Regazzetti, Anne; Dargère, Delphine; Auzeil, Nicolas; Gil, Sophie; Evain-Brion, Danièle; Laprévote, Olivier; Rat, Patrice
Abstract: Our aim was to study the toxicity of benzo(a)pyrene (BaP), an environmental pollutant that can reach placenta, on two human placental models in order to propose biomarkers in risk assessment for pregnancy. Ex vivo human placental cells isolated from term placenta and JEG-3 cancer cell line were incubated with BaP at 0.1–10 μM for 48 h or 72 h. BaP induced neither loss of cell viability nor apoptosis in ex vivo placental cells. To go further, we performed experiments on JEG-3 cell line that provides near-unlimited cells. The results we obtained in JEG-3 cells confirmed that BaP, in our experimental conditions, is neither necrotic nor apoptotic for placental cells. BaP toxicity on placental cells resulted in cell cycle arrest (G2/M phase) associated with inhibition of cell proliferation. Besides, we observed that BaP remodeled the protein content of membrane microdomains via increased expression of ZO-1, caveolin-1 and P2X7 cell degenerescence receptor. In conclusion, we identified nuclear and membrane potential biomarkers of risks for placenta and then pregnancy. These potential biomarkers detected on placental cell lines could represent useful tools for toxicological studies. Graphical abstract: Highlights: Placenta has to be considered as a target organ that can be injured by pollutants. We highlighted in vitro nuclear and membrane biomarkers of placental toxicity. Nuclear and membrane biomarkers represent useful tools for toxicological studies.